1989
DOI: 10.2136/sssaj1989.03615995005300030002x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Ultramicroscopic Porosity of an Oxisol as Determined by Image Analysis and Water Retention

Abstract: Detailed analysis of soil porosity in an Oxisol from Brazil was performed by image analysis in order to understand the unique water retention behavior of Oxisols. In addition to pores, the quantification of skeleton grains and plasma was made by image analysis of thin section micrographs. Due to the high quantity of skeleton grains and micro‐aggregates, interaggregate pores formed a network of interconnected simple and compound packing voids. Interaggregate porosity was an average of 39% for the profile. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 0 publications
1
6
0
5
Order By: Relevance
“…(1999) found that microporosity was unaffected by tillage practices. Curmi et al (1994) found that compaction had no effect on intra-aggregate pores of <1 µm diameter because their number is determined only by soil mineralogy (Bui et al, 1989). Our results are consistent with these observations.…”
Section: Discussionsupporting
confidence: 91%
“…(1999) found that microporosity was unaffected by tillage practices. Curmi et al (1994) found that compaction had no effect on intra-aggregate pores of <1 µm diameter because their number is determined only by soil mineralogy (Bui et al, 1989). Our results are consistent with these observations.…”
Section: Discussionsupporting
confidence: 91%
“…Celle-ci se caractérise essentiellement par la malnutrition protéino-calorique et le niébé, de par sa teneur en protéine, peut constituer un substitut aux produits carnés qui ne sont pas à la portée de la plus grande partie des habitants dans cette partie du monde. Cependant, la production du niébé, rencontre quelques contraintes notamment l'état de fertilité des sols en ce qui concerne la situation de l'élément phosphore, pourtant jouant un rôle important dans le développement de cette culture (Falisse H., et Lambert J., 1995 (Bui et Al., 1989 ;Bartoli et al, 1992 ;Sanchez et Logan, 1992 ;Buresh et al, 1997 ;Decker, 1999 ;Neufeldt,1999). Ce type de sols a une faible rétention en eau, cela est due à la présence d'une grande macroporosité liée à la microstructure stable résultant d'oxyhydroxydes chargés positivement et de Kaolinite mélangée à la matière organique chargé négativement (Bui et Al., 1989 ;Bartoli et al, 1992).…”
Section: Résumeunclassified
“…Cependant, la production du niébé, rencontre quelques contraintes notamment l'état de fertilité des sols en ce qui concerne la situation de l'élément phosphore, pourtant jouant un rôle important dans le développement de cette culture (Falisse H., et Lambert J., 1995 (Bui et Al., 1989 ;Bartoli et al, 1992 ;Sanchez et Logan, 1992 ;Buresh et al, 1997 ;Decker, 1999 ;Neufeldt,1999). Ce type de sols a une faible rétention en eau, cela est due à la présence d'une grande macroporosité liée à la microstructure stable résultant d'oxyhydroxydes chargés positivement et de Kaolinite mélangée à la matière organique chargé négativement (Bui et Al., 1989 ;Bartoli et al, 1992). Cette situation a comme conséquence, la carence en eau dont souffrent les plantes pendant les périodes sèches de la saison de pluie, malgré des teneurs en argile élevées (Neufeldts, 1999).…”
Section: Résumeunclassified
“…This may be an acceptable approximation in unstructured media with a narrow pore size distribution, such as sandstones. However, in structured soils, where the pore size distribution covers four or more orders of magnitude [Bui et al, 1989], the larger pores (e.g., macropores) may be connected to thousands or millions of small pores. Such a topological structure is clearly impossible on a regular lattice of small (4-14) coordination number.…”
Section: Limitations Of Pore Scale Network Modelsmentioning
confidence: 99%